Coronavirus disease 2019 vaccination uptake and hesitancy among Polish patients with inborn errors of immunity, autoinflammatory syndromes, and rheumatic diseases: A multicenter survey - Więsik-Szewczyk, Ewa; Ziętkiewicz, Marcin; Będzichowska, Agata; Napiórkowska-Baran, Katarzyna; Matyja-Bednarczyk, Aleksandra; Felis-Giemza, Anna; Jahnz-Różyk, Karina (Frontiers in Immunology, 2022)
Data regarding the willingness of patients affected by inborn errors of immunity to accept vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are limited. Therefore, this study assessed SARS-CoV-2 vaccination coverage and hesitancy in immunodeficient patients by surveying adults with primary immune deficiencies and autoinflammatory and rheumatic diseases on biologic therapy. The study was conducted from September 20, 2021, to January 22, 2022, when the primary coronavirus disease 2019 (COVID-19) vaccinations were available to all adults in Poland. We included 207 participants consecutively recruited from five referral centers (57% female; median age: 42.6 [range: 18–76, standard deviation ± 14.70] years). Overall, 55% (n = 114), 17% (n = 36), and 28% (n = 57) of the patients had primary immune deficiencies, autoinflammatory diseases, and rheumatic diseases, respectively. Among the entire cohort, 168 patients (81%) were vaccinated, and 82% were willing to receive a booster dose. Patients with autoinflammatory diseases had the highest vaccination rate (94.4%). A strong conviction that it was the correct decision (72%), fear of getting COVID-19 (38%), and expert opinions (34%) influenced the decision to vaccinate. Among the unvaccinated patients, 33.3% had primary or vocational education (p <0.001). Furthermore, only 33% believed they were at risk of a severe course of COVID-19 (p = 0.014), and 10% believed in vaccine efficacy (p <0.001). They also doubted the safety of the vaccine (p <0.001) and feared a post-vaccination flare of their disease (p <0.001). Half of the unvaccinated respondents declared that they would consider changing their decision. Vaccination coverage in immunodeficient patients was higher than in the general Polish population. However, the hesitant patients doubted the vaccine’s safety, feared a post-vaccination disease flare, and had primary or vocational education. Therefore, vaccination promotion activities should stress personal safety and the low risk of disease flares due to vaccination. Furthermore, all evidence must be communicated in patient-friendly terms.